The testosterone prescribing practice of BMS menopause specialists. Issue 2 (June 2021) - Scott, A; Holloway, D; Rymer, J; Bruce, D
The NICE Guidelines published in 2015 state that testosterone supplementation can be considered for menopausal women with low sexual desire if hormone replacement therapy alone is not effective. There is however, no detail on what to prescribe, how much to prescribe or whether monitoring is required. At the time of conception of this project, there was no national guideline or official advice from the British Menopause Society. We decided to ask menopause experts from around the UK to see if a consensus could be reached about good prescribing practice. The method and results as discussed below may be helpful in future recommendations and guidance.